2015
DOI: 10.2136/vzj2014.11.0162
|View full text |Cite
|
Sign up to set email alerts
|

Pore Tortuosity and Wettability as Main Characteristics of the Evolution of Hydraulic Properties of Organic Growing Media during Cultivation

Abstract: Irrigation in soilless culture is generally managed by taking into account the air-illed porosity and water availability of the growing medium for plants, which are determined before culture from the water retention curve. However, many factors can affect the physical properties during the growth period and then lead to poor irrigation. This study aimed to analyze the combined effects of root development and irrigation management on the hydraulic properties of organic media and their consequences for water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
7
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
8
7
2
Order By: Relevance
“…This can likely lead to changes in these physical properties, and then in water, air and nutrient availability for plant, with a risk to lead to a poor fertigation management, and then decreases in plant yield and/or quality, or more irremediable crop failures. Kerloch and Michel (2015), in their last paper, reported and confirmed previous works showing these changes in physical properties during time, with contradictory effects observed according to particle size distributions of the growing media. All authors mentioned decreases in air-filled porosity and pore tortuosity because of root growth in the macroporosity progressively filled by them (Allaire-Leung et al, 1999;Nkongolo and Caron, 2006;Caron et al, 2010;Cannavo and Michel, 2013;Kerloch and Michel, 2015).…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…This can likely lead to changes in these physical properties, and then in water, air and nutrient availability for plant, with a risk to lead to a poor fertigation management, and then decreases in plant yield and/or quality, or more irremediable crop failures. Kerloch and Michel (2015), in their last paper, reported and confirmed previous works showing these changes in physical properties during time, with contradictory effects observed according to particle size distributions of the growing media. All authors mentioned decreases in air-filled porosity and pore tortuosity because of root growth in the macroporosity progressively filled by them (Allaire-Leung et al, 1999;Nkongolo and Caron, 2006;Caron et al, 2010;Cannavo and Michel, 2013;Kerloch and Michel, 2015).…”
Section: Introductionsupporting
confidence: 78%
“…Kerloch and Michel (2015), in their last paper, reported and confirmed previous works showing these changes in physical properties during time, with contradictory effects observed according to particle size distributions of the growing media. All authors mentioned decreases in air-filled porosity and pore tortuosity because of root growth in the macroporosity progressively filled by them (Allaire-Leung et al, 1999;Nkongolo and Caron, 2006;Caron et al, 2010;Cannavo and Michel, 2013;Kerloch and Michel, 2015). However, Caron et al (2010) and Cannavo and Michel (2013) showed the decrease in the resulting relative gas diffusivity for fine growing media, whereas Allaire-Leung et al (1999), Cannavo and Michel (2013), and Kerloch and Michel (2015) reported its increase for coarser materials used in their trials (peat, pine bark, coco, and wood fiber).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In containerized soilless crop production, the volume of roots can become as important as the volume of the solid phase in the substrate, and it is easy to understand that during plant growth, fluid transfers properties are deeply modified. Kerloch and Michel (2015) studied the combined effects of root development and irrigation management on the hydraulic properties of sphagnum peat, coir, wood fiber, and bark. The authors found that aeration increased with time as a result of decreased pore tortuosity with increasing effective gas diffusion in all media.…”
Section: Properties Of Growing Media Used In Greenhouses and Nurseriesmentioning
confidence: 99%